KOMPOSIT HIBRID POLIESTER YANG DIPERKUAT SERAT Agave Cantala DAN TGFR L-4400 = Polyester Hybrid Composite Reinforced with Agave Cantala and Tgfr L-4400 Fibers - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The use of hybrid fibers in a matrix material could gives more various superiority than that using one type of fibers. The purpose of this research is to investigate the tensile and impact strengths of polyester hybrid composites reinforced with Agave Cantata and TGFR L-4400 fibers. Composite test specimens were made using hand lay-up method on glass dies. Continous unidirectional fibers were used in composite with 0Â° fiber orientation. Tensile and impact tests were applied to the composite specimens with 0.2 to 0.5 fiber volume fraction. Surface fracture of the specimen was observed using stereozoom microscope. The tensile and impact strengths for 0.5 fiber volume fraction hybrid composites were found to be 412 MPa and 307 kJ/m2, respectively. The results of this research indicate that tensile and impact strengths of polyester hybrid composites reinforced with Agave Cantata and TGFR L-4400 fibers containing up to 0.5 fiber volume fraction, increase with increasing fiber volume fraction . There is positive hybrid effects on mechanical properties of hybrid composites.